Inhibition of Na+/K+- and Ca2+-ATPase activities by phosphotetradecavanadate - Fraqueza, Gil (2019)
Polyoxometalates (POMs) are promising inorganic inhibitors for P-type ATPases. The experimental models used to study the effects of POMs on these ATPases are usually in vitro models using vesicles from several membrane sources. Very recently, some polyoxotungstates, such as the Dawson anion [P2W18O62]6-, were shown to be potent P-type ATPase inhibitors; being active in vitro as well as in ex-vivo. In the present study we broaden the spectrum of highly active inhibitors of Na+/K+-ATPase from basal membrane of epithelial skin to the bi-capped Keggin-type anion phosphotetradecavanadate Cs5.6H3.4PV14O42 (PV14) and we confront the data with activity of other commonly encountered polyoxovanadates, decavanadate (V10) and monovanadate (V1). The X-ray crystal structure of PV14 was solved and contains two trans-bicapped α-Keggin anions HxPV14O42(9-x)-. The anion is built up from the classical Keggin structure [(PO4)@(V12O36)] capped by two [VO] units. PV14 (10 μM) exhibited higher ex-vivo inhibitory effect on Na+/K+-ATPase (78%) than was observed at the same concentrations of V10 (66%) or V1 (33%). Moreover, PV14 is also a potent in vitro inhibitor of the Ca2+-ATPase activity (IC50 5 μM) exhibiting stronger inhibition than the previously reported activities for V10 (15 μM) and V1 (80 μM). Putting it all together, when compared both P-typye ATPases it is suggested that PV14 exibited a high potential to act as an in vivo inhibitor of the Na+/K+-ATPase associated with chloride secretion.